TOUCHLESS TRASH CAN PENUTUP SAMPAH AKAN TERBUKA OTOMATIS JIKA ADA TANGAN ATAU ORANG YANG MENDEKAT - Bayu Ramadhan; Riana Isnaeni; Ryana Mutiara Ni’mah; Tateng Sukendar (Ensiklopedia Research and Community Service Review, 2026)
The research on automatic trash bins aims to create an innovative solution for maintaining environmental cleanliness by designing an Arduino-based trash bin. This automatic trash bin is expected to reduce the negative impact of a dirty environment on human health and surrounding cleanliness. The trash bin consists of two main components: hardware and software. The hardware includes an ultrasonic sensor that detects objects at a certain distance and a servo motor that operates the lid of the trash bin. The software uses Arduino IDE to control and manage the functions of the hardware. This research employs a Prototype method, which allows for better control over the design and development process. With this method, researchers can quickly iterate and make improvements based on testing results and feedback. The results show that the automatic trash bin functions as expected. When the ultrasonic sensor detects an object at a distance of 20cm, the Arduino instructs the servo motor to automatically open the trash bin lid. Conversely, if the object is no longer detected, the lid will close again. The implementation of this Arduino-based automatic trash bin is expected to be an effective step in creating a cleane.Keywords: Arduino, Trash Can, Ultrasonic Sensor